Radiolabeled heterobivalent peptidic ligands: an approach with high future potential for in vivo imaging and therapy of malignant diseases - Fischer, Gabriel; Schirrmacher, Ralf; Wängler, Björn; Wängler, Carmen (ChemMedChem, 2013)
Two-pronged synergism: We review the recently developed approach of using heterobivalent peptide ligands that interact concomitantly with different receptors on tumor cells. These ligands exhibit highly favorable tumor-targeting properties and pave the way for the development of drugs for specific, sensitive, and noninvasive tumor imaging and therapy.
Gesehen am 31.03.2022